Evaluation of green roof characteristics in green building assessment - Sekulić, Mirjana B.; Stanković, Bojana D; Jovanović Popović, Milica (Arhitektura i urbanizam, 2014)
Methodology of building evaluation based on green building characteristics is rapidly gaining momentum, mainly in foreign, but also in domestic building practice. This methodology is being carried out through different Green Building Certification Systems, which are complex evaluation mechanisms based on numerous criteria of sustainability, addressing both ecological issues, but also economic and social ones. Green roof represents one of the “must have” features of contemporary buildings aiming to gain green label. This paradigm is based on their numerous characteristics which contribute to different aspects of building sustainability, among which are savings in energy and water consumption, but also ecological balance and quality of built environment. Criteria used for evaluation of green roof solutions and their overall contribution to the building, are integral part of all of the mentioned certification systems, but the way they are structured and formulated inside each system varies significantly, hence causing differences in evaluation results. This paper presents the analysis of green roof related criteria of three characteristic green building certification systems: LEED, BREEAM and CASBEE. These systems are chosen primarily because of the different evaluation methodology, but also because of their market prevalence and perspectives of usage in the domestic practice. Conclusions driven from these analyses and comparisons provide insight into main aspect of green roof planning and construction which are relevant for the overall building sustainability assessment.